Performance and inorganic fouling of a submergible 255 L prototype microbial fuel cell module during continuous long-term operation with real municipal wastewater under practical conditions. (December 2019) - Hiegemann, Heinz; Littfinski, Tobias; Krimmler, Stefan; Lübken, Manfred; Klein, Daniel; Schmelz, Karl-Georg; Ooms, Kristoffer; Pant, Deepak; Wichern, Marc
Graphical abstract: Highlights: A submergible 255 L prototype MFC module was operated under practical conditions. The biggest ever-investigated scale multi-panel SS/AC cathodes were utilized. Initially, good electrochemical performance and nutrient removal was achieved. Severe inorganic fouling decreased power density about 91 % within 77 days. Mechanical cleaning did not restore performance. Abstract: A submergible 255 L prototype MFC module was operated under practical conditions with municipal wastewater having a large share in industrial discharges for 98 days to investigate the performance of two of the largest, ever investigated multi-panel stainless steel/activated carbon air cathodes (85 × 85 cm). At a flow rate of 144 L/d, power density of 78 mW/m 2 Cat (317 mW/m 3 ) and COD, TSS and TN removal of 41 ± 16 %, 36 ± 16 % and 18 ± 14 %, respectively, were reached. Observed Coulombic efficiency and substrate-specific energy recovery were 29.5 ± 14 % and 0.184 ± 0.125 kWhel /kgCOD, deg, respectively. High salt content of wastewater (TDS = 2.8 g/L) led to severe inorganic fouling causing a drastic decline in power output and energy recovery of more than 90 % in the course of experiments. Mechanical cleaning of the cathodes restored only 22 % (17 mW/m 2 Cat ) of the power output and did not improve nutrient removal or energy recovery.